The Effect of Facilities, Price Perceptions, Location, and Word of Mouth on The Decision to Rent an Apartment at Cibubur Village Apartment East Jakarta - Sindi Claudia Vanessa; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
Cibubur Village Apartment is a vertical residence with five towers and 15 floors and has several functions, such as a place to live or for family vacations, business tourists, backpackers, and so on. This study aims to analyze the effect of facilities, price perceptions, location, and word of mouth on the decision to rent an apartment at Cibubur Village Apartment East Jakarta. A total of 104 respondents were selected using the purposive sampling method, which then collected data through questionnaires distributed and managed by the author. The data obtained was processed based on a statistical approach with the help of SPSS software version 26. The findings in this study indicate: 1) Facilities affects rental decisions positively and significantly, 2) Price perceptions affects rental decisions positively and significantly, 3) Location affects rental decisions positively and significantly, Word of mouth affects rental decisions positively and significantly. At the end of the research, the author presents a number of recommendations or suggestions to the Cibubur Village Apartment and also Kenny Jia Property to pay more attention to the facilities they have, ensure the right or appropriate rental prices, convince consumers about the location of the apartment itself, and improve service to consumers so that can win the word of mouth business competition. So that consumer decisions to rent apartments there are increasing every year.